Бүс нутгийн интеграцид дулдуйдан хөгжих нь Монгол Улсын ирээдүйн амжилтын түлхүүр мөн - С, Пауст (Journal of International Studies, 2013)
English title: Development Relied on Regional Integration is a Key to the Future Success of Mongolia